Pertencimento afro numa formação para ERER na escola: pesquisa pretagógica numa comunidade negra do interior do Ceará (Macaco/Itapipoca) - Silva Júnior, Francisco Manoel da (2024)
This research was carried out with teachers from the Josefa Pereira de Sousa school (infant/elementary), in the Community of Macaco, in the municipality of Itapipoca/State of Ceará/Brazil. This is training research, which took place between March and November 2023 with 10 women teachers and 2 male teachers, through five training meetings, which had Pretagogy as an approach. The starting point of the research was the desire to contribute to the community my family belongs to, based on the problem of difficulties that teachers at the Josefa Pereira de Sousa school encounter in carrying out pedagogical actions that comply with Law 10.639/2003. Even though it is a black community presenting factors of quilombamento (territory originated by three black families in 1910, who fought hard for the settlement of their descendants, name of the school honoring the community's ancestor, maintenance to this day of several significant elements of the material and immaterial Afro Brazilian cultural heritage), the school's curriculum suffers from the very low representation of content from Afro-Brazilian and African history and culture, these are not even mentioned in the current PPP (political- pedagogical project), contradicting 20 years of existence of a legal framework requiring mandatory provision. Certainly, part of teaching staff at the school report having carried out pedagogical practices that refer to Afro-Brazilian culture, however this was done in a timid and punctual manner, without qualified support in terms of training or well-founded didactic and paradidactic material. We know that such neglect of ERER implementation is common in Brazil where 77% of municipalities in 2023 have not yet incorporated it into curriculum (Alana/Geledés : 2023). Therefore, in 2024, one of the priorities placed by SECADI (Secretariat for Diversity) is to guarantee training in ERER for management and teaching staff, as well as monitoring the results, which are still so lacking today. Within the scope of this research, our focus was limited to strengthening the African sense of belonging of the school's teaching staff, as we noticed the difficulty that the majority demonstrate in identifying and valuing their Afro-knowledge, this aspect being an obstacle that Pretagogia has learned to face in an efficient way. This reality led us to the following questions: What elements of Afro belonging and markers of Africanities are present in the daily lives of teachers in this black community? Relatedly: What does a pretagogical training aimed at identifying the teaching staff's Afro-knowledge raise, in terms of understanding the importance and motivation for implementing the ERER? Thus, the main objective was: - to carry out pretagogical research aimed at strengthening the Afro-Brazilian belonging of the teaching staff at the studied school. The specific objectives were: - to use the example of my own belonging and previous relationship with this community as a pre-step for carrying out a survey of the Afro-knowledge of the group in training; - use pretagogical instrumentals so that teachers identify and value their particular history based on the dimensions of Africanities present in the black community to which they belong; – contextualize the ERER and the legal framework of the corresponding Guidelines, contributing to the understanding of the importance of these achievements for the black population – to serve as a stimulus for the group of teachers at the Josefa Pereira de Sousa school to effectively ( re )start the implementation of ERER in that school. From a methodological point of view, the following steps were carried out: - historical contextualization of ERER and Pretagogia - presentation of the researcher's Afro-knowledge through the instrumentals Tree of Afro-knowledge and My Music, My Belonging; application of these methodologic tools, with the teaching group of studied school to dialogue about the characteristics of their Afro belonging, study of the book Pretagogia by Professor Sandra Petit; planning pedagogical activities with textbook and infant/juvenil literature.The bibliographic dialogue was with the following reading references: Sandra H. Petit (2011), Henrique Cunha Jr (2011), Alecsandro Ratts (2011), Kabengele Munanga (2005), Geranilde Costa e Silva (2013), Rebeca de Alcântara e Silva Meijer (2012) Maria Kellynia Farias Alves (2015), Amadou Hampâté Bâ (2003), Claudia Oliveira da Silva (2016), Nilma Gomes (2011), among other reference people in the area of Pretagogy , Ethnic Racial Education and Africanities in general. From the point of view of the findings, despite the limited training time, the richness of elements of the local Afro-Brazilian and Afro-Cearense heritage was evident and this local cultural heritage is enough to support a future implementation of ERER in schools, based on the great diversity of Afro-knowledge and markers of their own teaching staff and students, which will require collective decision-making to focus more on ERER in the PPP, in theory and in practice. Also, it was understood that the Itapipoca Department of Education needs to express its political will for the effective implementation of the mandatory legal curriculum for Afro-Brazilian and African content in schools, and must also seek to qualify its actions in line with the needs already diagnosed by the National Educational Policy in terms of ERER, with experienced NEABs (ethnic racial groups of studies) from the state of Ceará being partners to be considered in this policy.